Gambaran Pengetahuan dengan Sikap Remaja Tentang Seksual Pranikah di SMA Al Islam Krian sidoarjo: Description of Knowledge with Teenagers' Attitudes About Premarital Sexuality at Al Islam Krian High School, Sidoarjo - Nuriyanah, Titin Eka (Jurnal Kebidanan Midwiferia, 2016)
Sex before marriage is sex behavior doing without legal marriage process according to conduction or religion and self tradition. The adolescent knowledge about sex before marriage must to know at young, in order to adolescent not missed perception about sex before marriage. The reality from 2009-2010 sex before marriage to ascent 29%. The purpose of study to know description of knowledge and adolescent about sex before marriage.Research desaign use description method and population is 40 student in Al Islam senior high school Krian Sidoarjo and all of them become research subject, primary data collected by given questioner. The data input in frequency tabulation and cross tabulation and than explained by narration without statisticaly test.The research of result showed that majority of 40 maleand female adolescent students had good knowledge as many as 22 (55%) with negative attitudes as many as 33 (82,5%). Wherease based on cross tabulation the adolescent whose has good knowledge has positive attitude (12,5%) and whose has enough knowledge has negative attitude (35%).The conclutions of this research knowledge and attitudes of adolescent about sex before marriage majority had good knowledge with negative attitudes. School area adviced to give information about sex before marriage at young